2011
DOI: 10.1371/journal.pone.0018919
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Histone Binding Ability Characterizations of Human PWWP Domains

Abstract: BackgroundThe PWWP domain was first identified as a structural motif of 100–130 amino acids in the WHSC1 protein and predicted to be a protein-protein interaction domain. It belongs to the Tudor domain ‘Royal Family’, which consists of Tudor, chromodomain, MBT and PWWP domains. While Tudor, chromodomain and MBT domains have long been known to bind methylated histones, PWWP was shown to exhibit histone binding ability only until recently.Methodology/Principal FindingsThe PWWP domain has been shown to be a DNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
174
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(185 citation statements)
references
References 52 publications
11
174
0
Order By: Relevance
“…This is close to but slightly further into the gene body than where the mammalian homolog MOZ/MORF is predominantly found, 400 bp downstream of the TSS (Lalonde et al 2013). This 59 shift in MOZ/MORF localization could be due to the mammalian complex's reduced affinity for H3K4me1 (Champagne et al 2008) (Table S1) and H3K36me3 (Vezzoli et al 2010;Wu et al 2011) (Table S1), resulting in a much greater dependence on H3K4me2/3 for recruitment to chromatin. The differing methyl-histonebinding properties of NuA3 and MOZ/MORF coincide with differing genome-wide localization of H3K4me1 and H3K36me3.…”
Section: Discussionmentioning
confidence: 87%
“…This is close to but slightly further into the gene body than where the mammalian homolog MOZ/MORF is predominantly found, 400 bp downstream of the TSS (Lalonde et al 2013). This 59 shift in MOZ/MORF localization could be due to the mammalian complex's reduced affinity for H3K4me1 (Champagne et al 2008) (Table S1) and H3K36me3 (Vezzoli et al 2010;Wu et al 2011) (Table S1), resulting in a much greater dependence on H3K4me2/3 for recruitment to chromatin. The differing methyl-histonebinding properties of NuA3 and MOZ/MORF coincide with differing genome-wide localization of H3K4me1 and H3K36me3.…”
Section: Discussionmentioning
confidence: 87%
“…H3K36me3 and SETD2 have been demonstrated to regulate both transcriptional elongation and alternative splicing events (Wagner and Carpenter, 2012). Several proteins have been reported to read H3K36me3 modifications by virtue of possessing a PWWP domain, including DNMT3a and Brpf1 (Dhayalan et al, 2010;Vezzoli et al, 2010;Wu et al, 2011). A recent report described for the first time, a reader for H3.3-specific K36me3 called BS69/ZMYND11 (Wen et al, 2014c).…”
Section: H33k36m and Tumorigenesismentioning
confidence: 99%
“…It is also worth noting that the majority of previously identified readers and enzymes were discovered using H3.1 histone substrates. For instance, from a focused structure and thermodynamics study, several PWWP domains were reported to bind H3.1K36me3 but with very low affinity (K D values in the mM range) (65). These observations collectively raise the possibility that some of these readers could have a higher affinity for variant histones and are in fact variant histone binders.…”
Section: More Histone Variant Readers?mentioning
confidence: 99%